Stapedotomy and its effect on hearing — our experience with 54 cases - Adedeji, Taiwo Olugbemiga (Afr Health Sci, 2016)
INTRODUCTION: This study reviews the cases of stapedotomy and evaluates its effectiveness at improving hearing loss in patients with otosclerosis. MATERIALS AND METHODS: Retrospective review of patients' records who had clinical and audiometric diagnosis of otosclerosis from January to December 2012 RESULTS: A total of 54 stapedotomy surgeries (52 unilateral and 1 bilateral surgeries) were received. Average post-operative ABG for 0.5, 1, 2 and 4 KHz showed that 61.1% had complete closure of ABG ( ABG < 10 dB) compared with 1.6% preoperatively and 85.2% had closure of ABG to within 20dB compared with 4.7% preoperatively (t − 13.89, p = 0.000). More than 94% had hearing improvement and 81.5% had ABG closure greater than 10 dB postoperatively (mean gain 23.38 ± 12.37, t = 13.89, p = 0.000). A total of 13% complications were recorded with TM perforation (5.6%) being the commonest complication. CONCLUSION: Stapedotomy is an effective surgical procedure for the treatment of otosclerosis which leads to improvement in patients' quality of life. A favorable hearing outcome can be obtained by the combination of experienced hands with minimal surgical trauma and appropriate surgical technique.